The Integrating Islamic Values in The Mathematics Education Curriculum at UIN Saizu Purwokerto - Ulpah, Maria; Setiani, Riris Eka; Ramadani, Nabila (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Integrating Islamic values ​​in the mathematics education curriculum is an effort to form mathematical concepts with ethical and spiritual principles in Islam. This approach aims to provide a more holistic learning experience, developing cognitive skills and shaping students’ character and morals. This integration also encourages the understanding that mathematics is abstract and closely related to everyday life and Islamic teachings. By adopting this approach, mathematics education can be more relevant, meaningful, and contribute to forming students who are knowledgeable and have noble character. This study aims to analyze the integration of Islamic values ​​in the Mathematics Education curriculum. The data collection methods in this study are documentation of the Mathematics Education study program curriculum, guidelines for compiling an integrative curriculum, learning observations and interviews with lecturers and students. Data analysis techniques include data reduction, data presentation and drawing conclusions and verification. This study concludes that the integration of Islamic values ​​in the mathematics education curriculum starts from determining the profile of graduates, learning outcomes, the learning process and evaluation. In the learning process, this integration can be applied in creating teaching materials, the application of thematic and contextual learning and research by lecturers or students.